Effect of Innovation Capability on Marmer Supply Chain Performance: Case Study at Amazing Indonesian Alabaster - Azka Ainnur Rizki; Dessy Isfianadewi (PT SOLUSI EDUKASI BERDIKARI, 2023)
Amazing Indonesian Alabaster is an MSME company that managing marble raw materials into (home accessories). This internship was conducted using a quantitative approach. The work analysis unit analysis is on employees with permanent status and non-managerial at Amazing Indonesian Alabaster. Based on the analysis in the internship activities, it shows that: (1) Innovation capability has a positive effect on supply chain performance with a regression coefficient of 0,250; (2) based on arithmetic data the ability to innovate is referred to with an average of 3,52, meaning that the individual factors of employees factor is highly approved to be applied at Amazing Indonesian Alabaster because employees have a high ability to innovate characterized by the progress of innovation activities. Based on arithmetic data, supply chain performance performance is referred to as an average of 3,60, meaning that sales performance is in the category of high high level of sales in this company in the absence of the Covid-19 pandemic.